VALUASI EKONOMI WISATA PANTAI MATAKUS KECAMATAN TANIMBAR SELATAN - Ronaldo Gabriel Ruban; Renoldy Lamberthy Papilaya; Eygner Gerald Talakua (Universitas Pattimura, 2023)
The Matakus Beach is located in the Village of Matakus, South Tanimbar Subdistrict, Tanimbar Islands Regency (KKT), Maluku Province. This beach is situated on a small island with a total area of about 474 hectares and a circumference of 9,972 meters. Consequently, Matakus Island has promising prospects for development into an island tourism destination, necessitating an economic valuation. This research aims to determine the influence of travel costs to Matakus Beach on the interest to revisit, analyze the factors affecting the number of visits to Matakus Beach, and assess the economic value of Matakus Beach tourism. The basic research methods employed include survey, literature review methods and the data analysis is quantitative. The research findings indicate that the general characteristics of respondents show that tourists are predominantly aged 27-36 year with an average income of Rp 4.08 million per month. The results show travel costs amounting to Rp 32,615,000 per month. The analysis indicates that the variable with a significant relationship to the number of tourist visits is the travel cost variable, with a significance value of 0.004 smaller than 0.05 (0.004 <0.05), meaning that the number of tourist visits is mutually influenced by travel costs. The coefficient of determination (R²) is 0.624, indicating an independent variability of 62.4%. The economic value of Matakus Beach tourism is calculated at Rp 178,412,140 per month.